Cold case reviews : DNA, detective work and unsolved major crimes - Allsop, Cheryl (Oxford : Oxford University Press, 2018)
This text provides the first ethnographic account of a UK major crime review team, providing a comprehensive, conceptual account of cold case reviews not currently available from an academic criminological perspective. Cold case reviews are a relatively new and innovative form of policing yet, to date, there has been little empirical research into their conduct in the UK. Addressing this empirical void by shining a light on the practicalities and realities of cold case investigations, the author spent eight months with a major crime review team tasked with conducting 28-day reviews of 'live' unsolved murder and stranger rapes and detecting long term unsolved major crimes. The resulting work contains a unique focus on forensic science and the role of the National DNA Database (NDNAD) in cold case reviews, adding to the current debates about the police use of forensic science.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 20, 2018).
Keywords: Cold cases (Criminal investigation) -- Great Britain; True Crime; Social services & welfare, criminology